1987
DOI: 10.1073/pnas.84.6.1555
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of glycolate and D-lactate metabolism in a Chlamydomonas reinhardtii mutant deficient in mitochondrial respiration

Abstract: The possibility that glycolate oxidation in unicellular green algae is linked to mitochondrial electron transport, rather than to peroxisomal metabolism as in higher plants and animals, was studied in a mutant of Chlamydomonas reinhardtii (dk97) deficient in cytochrome oxidase. This mutant had normal rates of dark respiration (40 ± 15 ,umol of 02 uptake per hr per mg of chlorophyll) but had only 11% of wild-type levels of cytochrome oxidase activity. Salicylhydroxamic acid (SHAM) reduced the dark respiration r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Unlike plants, C. reinhardtii has been shown both to produce ( Husic and Tolbert 1985 ) and oxidize d -lactate ( Husic and Tolbert 1987 ). To identify potential d -LDHs in C. reinhardtii , the genome sequence was searched with sequences of well-characterized NAD + -dependent d -LDH enzymes ( d -nLDH; EC 1.1.1.28) from other species.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike plants, C. reinhardtii has been shown both to produce ( Husic and Tolbert 1985 ) and oxidize d -lactate ( Husic and Tolbert 1987 ). To identify potential d -LDHs in C. reinhardtii , the genome sequence was searched with sequences of well-characterized NAD + -dependent d -LDH enzymes ( d -nLDH; EC 1.1.1.28) from other species.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, none of the chlorophycean algae investigated possesses leaf peroxisomes (Stabenau 1972b, 1984, 1992a, b, 1994, Stabenau et al 1989). Their glycolate oxidizing enzyme is a dehydrogenase (Frederick et al 1973, Stabenau 1974a, b, Beezley et al 1976, Stabenau et al 1993) transferring electrons to a redox system of the mitochondrial respiratory chain (Paul and Volcani 1976, Husic and Tolbert 1987). All enzymes of the glycolate metabolism tested in the Chlorophyta are located in mitochondria (Stabenau 1972b, 1974a, b, 1984, 1994, Stabenau et al 1984a, 1989, 1993), although oxidation of glycolate was found to be also possible to some extent in chloroplasts of two algae (Goyal and Tolbert 1996, Goyal 2002).…”
Section: Introductionmentioning
confidence: 99%
“…An inability to keep the stroma more oxidized would tend to enhance the production of reactive oxygen species in the chloroplast, as suggested from the measurement of lipid hydroperoxides (Table I). In addition, perturbations to mitorespiration in stm6 might also inhibit photorespiration (61), which again could cause sensitivity to photoinhibition. The reduced levels of ATP in stm6 would also impair the normal ATP-dependent repair processes leading to the observed sensitivity of growth to high light.…”
Section: Moc1 Is Required For Appropriate Expression Of Mitochondrialmentioning
confidence: 99%